Cambridge igcse mathematics - Pimentel, Ric.; Wall, Terry ([S.l.] : Hodder Education, 2004)
The most cost effective and straightforward way to teach the latest (2015) syllabus, with all the core and extended content covered by a single book and accompanying free digital resources. This title is endorsed by Cambridge International Examinations for the latest Cambridge IGCSE Mathematics (0580) syllabus, for first teaching from 2013 and first examination 2016. - Gives students the practice they require to deepen their understanding through plenty of questions - Consolidates learning with unique digital resources on the CD, included free with every Student's Book.